School Facility Security: An Evaluation Of Surveillance Technologies And Efforts To Improve Physical Security - Adiyono, Adiyono; Mandasari, Kiti; N.A, Laila; Suryani, Nyayu Yayu (International Education Trend Issues, 2024)
by Muhammadiyah SMP Tanah Grogot, an educational institution in Indonesia, and identify areas for improvement. The study uses a case study method, which involves data collection through observation, interviews with school authorities, and reviewing relevant documents. The findings reveal that while the school has made significant efforts to improve physical security by implementing surveillance technology and access control systems, there are still areas that require improvement. The study recommends implementing a comprehensive emergency response plan, regular security audits, and staff training to ensure the effectiveness of physical security measures over time. The research provides practical insights that can be applied to other educational institutions facing similar challenges and highlights the importance of ongoing monitoring and evaluation to ensure the effectiveness of physical security measures. Identify the obstacles or barriers faced in the implementation of surveillance technology, efforts to improve physical security in schools, identify the success of surveillance technology in reducing security incidents in schools and increasing feelings of safety in schools, identify differences in the perception and effectiveness of surveillance technology between schools with different levels of resources and size, and the contribution of surveillance technology to the achievement of broader school security goals.